Tindak Tutur Ilokusi Teks Deklarasi Kemerdekaan Palestina - Safitri, Salsabila; Triwinarti, Wiwin (UI Scholars Hub, 2022)
This study discusses the types and functions of illocutionary speech acts contained in the text of the Palestinian Declaration of Independence. The text of the Palestinian Declaration of Independence was written by a Palestinian poet, Mahmoud Darwish and then read by the First President of Palestine Yasser Arafat in Algeria on November 15, 1988. This research was analyzed using qualitative descriptive methods and Searle's (1979) speech act theory. In the text of the Palestinian Declaration of Independence, the researcher found 14 utterances containing illocutionary speech acts with different functions. There are 4 assertive utterances with the function of stating, 3 directive utterances with the function of asking and inviting, 3 commissive utterances with the function of promising, 2 expressive utterances with the function of expressing disappointment and criticism, and 2 declarative utterances with the function of declaring the independence of Palestine and appointing the Palestine Liberation Organization (PLO) as the legitimate representative of Palestine.